Policy Matters But How? Explaining Non-Compliance Dynamics in the EU - Börzel, Tanja; Hofmann, Tobias; Panke, Diana (2011)
Abstract: The European Union’s infringement procedure is highly legalized. Nevertheless, as in other international institutions, non-compliance occurs on a regular basis and its transformation into compliance varies across EU infringement stages and over time. State of the art compliance literature focuses mainly on country-specific explanations, such as power, capacity, and legitimacy. In particular power-capacity models explain a good part of whether non-compliance occurs and how quickly it can be resolved. Yet, these approaches leave substantial parts of the empirical variation that we observe unexplained. This paper argues that policy and, in particular, rule-specific variables – although often neglected – are important for explaining non-compliance. Based on a quantitative analysis, we show that policy matters not only for the frequency with which EU law is violated, but also the persistence of non-compliance over time and over the different stages of the infringement procedure